Assessing the Influence of Local Rebar Strain Demand on the Cyclic Behavior and Repairability of Concrete Beams Reinforced with Steel and GFRP Rebars - Amir Azarpour; Saeed Tariverdilo; Mohammad Sheidaii (Journal of Rehabilitation in Civil Engineering)
Yielding of longitudinal rebars in reinforced concrete (RC) elements leads to the localization of damage and consequently increases repair costs. Two options are available to mitigate this localization in rebar strain: the use of debonded-steel rebars or Glass Fiber Reinforced Polymer (GFRP) rebars. An experimental program was devised, including three specimens with steel, debonded-steel, and GFRP rebars. There is a bold change in the crack pattern, from localized in the case of steel rebar with a crack width of 35 mm, to distributed cracks in the cases of debonded-steel and GFRP rebars, with a crack width smaller than 3 mm. This indicates a significant improvement in terms of repairability for these specimens. The failure drifts of the specimens are 3.5%, 3.5%, and 5.5%, respectively. Results also show that the debonding of steel rebars increases energy dissipation. This demonstrates that by following current practices in the design and construction of RC elements, and simply by debonding steel rebars, it is possible to decrease repair costs.